The beneficial effects of massage therapy for insomnia in postmenopausal women - H. Hachul; D.S. Oliveira; L.R.A. Bittencourt; M.L. Andersen; S. Tufik (Sleep Science, 2014)
With increases life expectancy, the incidence of undesirable manifestations of menopause has increased as well. The effects of lost ovarian function include progressive decrease in estradiol secretion, trophic changes in the breast, vasomotor symptoms, anxiety, depression, and sleep disorders. Insomnia, which has physiological consequences and can result in a loss of quality of life, is prevalent in women after menopause. Hormone therapy has been widely used to reduce menopausal symptoms, but its use in recent years has been questioned because of the reported risks of cardiovascular events and increased incidence of tumors. This controversy has generated significant interest in non-hormonal treatments among both physicians and patients. Our previous research has shown a positive effect of massage therapy on menopausal symptoms. We explored the hypothesis that massage therapy would produce beneficial effects in postmenopausal women through inflammatory and immunological changes. Recent results from self-report questionnaires have shown improvements in sleep pattern and quality of life following massage therapy. These findings demonstrate the effectiveness of massage therapy for the treatment of postmenopausal symptoms, particularly insomnia, and indicate that it is a promising line of research.